Validation of the hydrodynamics in a turbulent un-baffled stirred tank: A necessity for vortex-reactor precipitation studies. (16th March 2020) - Saikali, E.; Rodio, M.G.; Bois, G.; Bieder, U.; Leterrier, N.; Bertrand, M.; Dolias, Y.
Highlights: The turbulent flow in an un-baffled tank reactor is analyzed by CFD. As the flow is highly unsteady, a statistical convergence analysis is performed. The mesh refinement to reproduce correctly the mixing vortices is determined. Tangential velocity dominates the mixing, unlike to baffled tank reactors. LES data show a very good agreement versus theoretical predictions and experimental measurements. Abstract: This paper is devoted to large eddy simulations of a turbulent flow in an un-baffled stirred tank reactor with vortex effect. The work aims at providing reference solutions regarding the hydrodynamics and the different mixing regions. Such data serve in modelling the precipitation process that takes place in many chemical engineering applications. The numerical study is performed by the open source TrioCFD code that employs a discontinuous front-tracking algorithm to solve the free surface at the top of the reactor. A sufficiently converged mesh has been identified from a sensitivity analysis where a convergence at the same order of the employed numerical scheme has been recorded. The quality of the resolved fields confirm that the performed LES is good and that the mesh size is almost of the Taylor turbulent micro-scale order. The converged statistical fields have shown a good agreement with both the theoretical models and the experimental measurements.